1979
DOI: 10.1111/j.1432-1033.1979.tb04223.x
|View full text |Cite
|
Sign up to set email alerts
|

Desialized Low‐Density Lipoprotein Regulates Cholesterol Metabolism in Receptor‐Deficient Fibroblasts

Abstract: Binding of homologous low density lipoproteins (LDL) to specific cell-membrane receptors initiates regulation of cholesterol metabolism in normal human fibroblasts, but minor regulatory effects are observed in receptor-deficient cells. After enzymic removal of sialic acid residues, however, the desialized LDL aquires the ability to regulate cholesterol biosynthesis and cholesterol esterification in receptor-deficient cells as effective as native LDL in normal cells. This is indicated by a suppression of hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Malmendier et al (50) had observed that the removal of sialic acid from human LDL in vivo increased the rate of metabolic clearance. Similarly, Filipovic and Buddeck (51) found that removal of sialic acid residues accelerate the rate of internalization of the lipoprotein and subsequently the regulation of the metabolism of cellular cholesterol. In contrast, however, Melajarvi et al (52) have shown that sialic acid poor LDL is catabolized more slowly than the sialic acid rich LDL.…”
Section: Serum Sialic Acidmentioning
confidence: 91%
“…Malmendier et al (50) had observed that the removal of sialic acid from human LDL in vivo increased the rate of metabolic clearance. Similarly, Filipovic and Buddeck (51) found that removal of sialic acid residues accelerate the rate of internalization of the lipoprotein and subsequently the regulation of the metabolism of cellular cholesterol. In contrast, however, Melajarvi et al (52) have shown that sialic acid poor LDL is catabolized more slowly than the sialic acid rich LDL.…”
Section: Serum Sialic Acidmentioning
confidence: 91%
“…The carbohydrate moieties may play a role for the function, the antigenicity, and the circulatory life time of a plasma glycoprotein. In the case of the carbohydrate moieties of LDL, several studies have also been done, but the results remain controversial (11,12,13,14,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3C and D, association and degradation in WHHL rabbit fibroblasts was much lower than those in normal rabbit fibroblasts and there was no significant difference between the types of 125 I-LDL. Figure 4A and B showed [ 14 (8,9). We speculate that the variable activity of one or more of these processing enzymes might cause the variation of carbohydrate moieties, resulting in the change of the molar ratio of acidic sugar chains of apo B-100.…”
Section: Association Degradation and Cholesteryl Ester Formation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Kooistra et al [18] showed that positive charges play a dominant role in the uptake of ribonuclease (PI = 9.5) by sinusoidal rat liver cells. Also, arginine residues, as well as oligosaccharide moieties, contribute to the binding to endocytic receptors (on human fibroblasts) of the complex determinants present on low-density lipoproteins [19,20] and on a-L-iduronidase 1211. The second is compatible with the proposal of Chothia and Janin [22] that when insulin associates to form dimers the binding is dominated by hydrophobic interactions, and with the finding of Kahn et al [23] that the free-energy term in the binding of insulin to purified liver membranes is dominated by the entropy term.…”
Section: Discussionmentioning
confidence: 99%